Are agri‐environment schemes successful in delivering conservation grazing management on saltmarsh?. Issue 7 (23rd May 2019) - Mason, Lucy R.; Feather, Alastair; Godden, Nick; Vreugdenhil, Chris C.; Smart, Jennifer
Abstract: Grasslands occur around the globe and, in temperate regions, their natural management by fire, drought and wild herbivores has largely been replaced by grazing with domestic livestock. Successful management for agriculture is not always suitable for conservation and can have a detrimental effect on biodiversity. Conservation grazing of saltmarshes, delivered through agri‐environment schemes, may provide a solution to counteract biodiversity loss by providing farmers with financial incentives to graze these internationally important coastal wetlands more sensitively. To assess whether conservation grazing is being achieved and whether agri‐environment schemes are effective in delivering this management, we conducted a national survey on English saltmarshes, scoring the management on each site as optimal, suboptimal or detrimental in terms of suitability for achieving conservation aims for five aspects of grazing: presence, stock type, intensity, timing and habitat impact. Although most saltmarshes suitable for grazing in England were grazed, conservation grazing was not being achieved. Sites under agri‐environment management for longer did score higher and approached optimal levels in terms of grazing intensity in one region, but sites with agri‐environment agreements were no more likely to be grazed at optimal conservation levels than sites without them overall, indicating that agri‐environment schemes, in their current form, are an ineffective delivery mechanism for conservation grazing on saltmarsh. The low specificity of agri‐environment prescription wording may contribute to this failure, with prescriptions either being vague or specifying suboptimal or detrimental management objectives, particularly for grazing intensity, timing and stock type. These objectives are often set too high or too low, during unsuitable periods or using stock types inappropriate for achieving conservation aims. Synthesis and applications . Our national survey indicates that agri‐environment schemes are not currently delivering conservation grazing on English saltmarshes. Agri‐environment schemes are the only mechanism through which such grazing can be implemented on a national scale, so improving their effectiveness is a priority. Policymakers, researchers and managers need to work together to ensure better translation of conservation guidelines into schemes, increasing the specificity of management prescriptions and improving understanding of the need for management measures. A more detailed and reliable system of auditing to ensure that management activities are taking place would be beneficial or alternatively moving to a results‐based scheme where payments are made on desirable outcomes rather than on evidence of management. Abstract : Our national survey indicates that agri‐environment schemes are not currently delivering conservation grazing on English saltmarshes. Agri‐environment schemes are the only mechanism through which such grazing can be implemented on a national scale, so improving their effectiveness is a priority. Policymakers, researchers and managers need to work together to ensure better translation of conservation guidelines into schemes, increasing the specificity of management prescriptions and improving understanding of the need for management measures. A more detailed and reliable system of auditing to ensure that management activities are taking place would be beneficial or alternatively moving to a results‐based scheme where payments are made on desirable outcomes rather than on evidence of management.